2016
DOI: 10.1038/srep26934
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal gene transfer events reshape the global landscape of arm race between viruses and homo sapiens

Abstract: Horizontal gene transfer (HGT) drives the evolution of recipient organism particularly if it provides a novel function which enhances the fitness or its adaption to the environment. Virus-host co-evolution is attractive for studying co-evolutionary processes, since viruses strictly replicate inside of the host cells and thus their evolution is inexorably tangled with host biology. HGT, as a mechanism of co-evolution between human and viruses, has been widely documented, however, the roles HGT play during the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 67 publications
0
14
0
1
Order By: Relevance
“…Also, attention should be paid toward formulation quality control and assurancewhen VLPs are produced by (heterologous) expression they are devoid of their genome; however, they can oftentimes package host RNA causing unwanted side effects [235]. Mammalian viruses may also cause horizontal genetic transfer events evolving both humans and viruses in unimaginable ways [236]. These possibilities must be carefully examined and studied as well as regulated.…”
Section: Challenges Moving Forward and Future Directionsmentioning
confidence: 99%
“…Also, attention should be paid toward formulation quality control and assurancewhen VLPs are produced by (heterologous) expression they are devoid of their genome; however, they can oftentimes package host RNA causing unwanted side effects [235]. Mammalian viruses may also cause horizontal genetic transfer events evolving both humans and viruses in unimaginable ways [236]. These possibilities must be carefully examined and studied as well as regulated.…”
Section: Challenges Moving Forward and Future Directionsmentioning
confidence: 99%
“…The genome analysis results showed that Mesonia algae K4-1 may be more robust to variable conditions and equipped with an ecological advantage. Horizontal gene transfer (HGT) is a general way for bacteria to respond to different selective pressures and obtain an important competitive advantage (Chen et al, 2016). In HGT events, the acquisition or loss of MGE plays a key role in carrying functional genes that enhance fitness in the environment (Hall et al, 2017; Wang L. et al, 2017; Husnik and McCutcheon, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the BovB element moved at least 11 times between snakes, lizards, ruminants and marsupials (Ivancevic et al 2017) and the Mariner element moved between nematodes, arthropods, fungi, molluscs, vertebrates and plants [ (Palazzo et al 2019) and references therein]. Numerous stable introductions of virus DNA into the germline of various eukaryote species have also been reported (Katzourakis and Gifford 2010;Holmes 2011;Feschotte and Gilbert 2012;Chen et al 2016) . In vertebrates, endogenous retroviruses (ERVs) can insert into their host genome and generate copies of themselves through germline reinfections or retrotransposition events (Gilbert and Feschotte 2018;Greenwood et al 2018) .…”
Section: Probability Of Horizontal Transfer Of a Piece Of Dna Containmentioning
confidence: 99%